Estimation of effective porosity, Tirrawarra Sandstone, Cooper Basin, Australia. - Rezaee, M. Reza; Lemon, N. (CSIRO Publishing, 1997)
Estimation of effective porosity in shaly sand formations is the prime parameter for reserve calculation and for good understanding of the behaviour of a formation during production. The Late Carboniferous to Early Permian, fluvio-deltaic Tirrawarra Sandstone is a kaolinite-bearing sandstone and an important hydrocarbon reservoir in the Cooper Basin. Petrographic point count and image analysis data from 130 samples, together with data from about 650 core samples and wireline log data from 14 wells of the Tirrawarra Sandstone in the Moorari and Fly Lake Fields, have been used to estimate effective porosity from sonic log. Based on integration of all data and with the knowledge of the volume fraction of kaolinite and associated microporosity (20% for kaolinite masses in the Tirrawarra Sandstone in the studied samples) effective porosity can be expressed as: [formula]. On average, estimated effective porosity is 2 porosity units less than the total porosity and it varies for depositional environments which have different kaolinite contents.